How To Stop Worrying And Start Living - Carnegie, Dale (New Delhi : Rupa, 2016)
How to break the worry habit - before it breaks you. Worry affects everyone and influences your work, money, family life and relationships. This book offers practical suggestions for breaking out of this destructive habit and leading a more positive and enjoyable life. Worry-free tips include: fundamental facts you should know about worry -- A magic formula for solving worry situations -- Seven ways to cultivate a mental attitude that will bring you peace and happiness -- How to keep from worrying about criticism -- Six ways to prevent fatigue and worry -- Personal tips from those who have conquered worry
Keywords: Psychology - Self-realization